2021
DOI: 10.1177/1534734620988217
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Silver Nanoparticles Dressing (SilvrSTAT Gel) and Conventional Dressing in Diabetic Foot Ulcer Healing: A Prospective Randomized Study

Abstract: Background We are trying to evaluate silver nanoparticles’ effectiveness (SilvrSTAT Gel) in accelerating healing rate of nonischemic diabetic foot ulcers (DFUs). Methods This prospective, double-blind, randomized, controlled study includes 80 patients with nonischemic DFUs classified into 2 groups. Group A was subjected to SilvrSTAT Gel dressing, and group B was subjected to conventional dressing (wet-to-moist dressing with or without povidone-iodine). All cases had minimal debridement before treatment. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
1
15
0
8
Order By: Relevance
“…After the implementation of the hydrogel/nano silverbased dressing on patient's with DFU of the present study, the findings illustrated that use of hydrogel\nano silver wound dressing compared to the traditional dressing showed a more significant reduction in the area when the initial wound area is compared to the subsequent area measurements expressed as the initial percentage. The wound healing is in agreement with Essa et al 2021, who have recently compared silver Nanoparticles dressing and conventional dressing in diabetic foot healing, and their findings proved that the healing rate was statistically significant and the healing rate per week and the complete recovery was achieved with SliverSTAT group, around onefifth of the study sample by six weeks where the rest of the patients were healed from week eight to week twelve, whereas the conventional group the wound healing started from week eight to week twelve (31) .…”
Section: Discussionsupporting
confidence: 86%
“…After the implementation of the hydrogel/nano silverbased dressing on patient's with DFU of the present study, the findings illustrated that use of hydrogel\nano silver wound dressing compared to the traditional dressing showed a more significant reduction in the area when the initial wound area is compared to the subsequent area measurements expressed as the initial percentage. The wound healing is in agreement with Essa et al 2021, who have recently compared silver Nanoparticles dressing and conventional dressing in diabetic foot healing, and their findings proved that the healing rate was statistically significant and the healing rate per week and the complete recovery was achieved with SliverSTAT group, around onefifth of the study sample by six weeks where the rest of the patients were healed from week eight to week twelve, whereas the conventional group the wound healing started from week eight to week twelve (31) .…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, Wounds were healed spontaneously in 14 patients (70%) in group B patients and skin graft was successfully taken in 4 patients 20%. Essa reported that: After the implementation of the hydrogel/ nano silver-based dressing on patients with chronic leg ulcer of the present study, the findings illustrated that use of hydrogel\nano silver wound dressing compared to the traditional dressing showed a more significant reduction in the area when the initial wound area is compared to the subsequent area measurements expressed as the initial percentage and their findings proved that the healing rate was statistically significant and the healing rate per week and the complete recovery was achieved with Sliver STAT group, around one-fifth of the study sample by six weeks where the rest of the patients were healed from week eight to week twelve, whereas the conventional group the wound healing started from week eight to week twelve [12].…”
Section: Resultsmentioning
confidence: 89%
“…Healing in diabetic foot ulcers has been described at around 95.8% ( 26 ) , 85% ( 33 ) , 81.8% ( 27 ) , 71% ( 28 ) and a reduction of ±7 cm ( 18 ) , pressure sores at 16.4% ( 29 ) and a reduction of ±15 cm ( 20 ) ; leg ulcers a reduction of ±5 cm ( 19 ) and a reduction of 43 days in treatment time ( 35 ) ; venous ulcers healing was 92.8% ( 22 ) , 86.4% ( 30 ) ; surgical wounds healing was 93% ( 31 ) and burns 90.7% ( 24 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The technological advance inherent in the development of nanotechnology strengthens and disseminates in the academic field technological possibilities for resolving preponderant issues in the field of health ( 37 ) . The manufacture of nanocomposites for the health care of patients with skin lesions is being explored with this nanotechnological development, resulting in the supply of synthetic dressings with silver nanoparticles ( 21 , 24 , 32 , 36 ) , biomaterials with nanocrystalline silver ( 27 , 34 ) , nanofibers loaded with bioactive substances ( 16 , 18 , 19 , 30 , 35 ) , nanofibers loaded with growth factors ( 17 , 28 ) or even synthetic dressings with growth factors ( 25 ) , hydrogels with growth factors ( 26 ) , nanogels ( 23 , 33 ) , nanoemulsions ( 31 ) and the possibility of associating adjuvant therapies with nanocomposites ( 22 , 29 ) .…”
Section: Discussionmentioning
confidence: 99%